PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ANDROID PADA MATERI TEKNOLOGI INFORMASI DAN KOMUNIKASI KELAS X DI SMKN 3 PADANG - Monita, Sri Devi; Mulyono, Heri; Devegi, Mourend (Universitas Muhammadiyah Tapanuli Selatan, 2025)
In the study of computer science, the use of learning aids is important. In Class X MPLB SMKN 3 Padang, information was obtained that there were several obstacles in the Computer Science learning process. These obstacles include the limited use of teaching materials, the materials used are only sourced from the internet and sometimes use presentation media. The research goal that is expected to be achieved by designing Android-based learning media for computer science subjects is to create valuable and practical learning media. This research method uses research and development (RD) methods. The results of the research The validity of the media content was 80.36% with the category